Tragopogon anatolicus (Asteraceae), a new species from east Turkey - Dogan Beki̇r; Duran, Ahmet; Gültepe, Mutlu; Öztürk, Meryem; Coşkunçelebi̇ Kami̇l (Phytotaxa, 2014)
The new species, Tragopogon anatolicus A.Duran, B.Doğan & Coşkunç. sp. nov. (Asteraceae) is described and illustrated from Cilo Mt. (Hakkari), south-east Anatolia, Turkey. Tragopogon anatolicus is a local endemic, most similar to T. buphthalmoides (DC.) Boiss. Diagnostic morphological characters of these two closely related taxa are discussed. A phylogenetic analysis based on nrDNA ITS sequence data indicated that T. buphthalmoides is the sister species of the new taxon. Ecology, biogeography and conservation status of the new species are also presented.